Novel Antibiotic Testing Approaches Reveal Reduced Antibiotic Efficacy Against Shiga Toxin-Producing Escherichia coli O157:H7 Under Simulated Microgravity - Kim, Hye Won; Rhee, Min Suk (Frontiers in Microbiology, 2018)
As a foodborne and environmental pathogen, Shiga toxin-producing Escherichia coli O157:H7 could pose a health threat to immunocompromised astronauts during a space mission. In this study, novel approaches, including real-time testing and direct evaluation of resistance mechanisms, were used to evaluate antibiotic efficacy against E. coli O157:H7 under low-shear modeled microgravity (LSMMG) produced using a rotary cell culture system. When compared with normal gravity (NG), bacterial growth was increased under LSMMG in the presence of sub-inhibitory nalidixic acid concentrations and there was an accompanying up-regulation of stress-related genes. LSMMG also induced transcriptional changes of the virulence genes stx1 and stx2, highlighting the potential risk of inappropriate antibiotic use during a spaceflight. The degree of bacterial cell damage induced by the antibiotics was reduced under LSMMG, suggesting low induction of reactive oxygen species. Efflux pumps were also shown to play an important role in these responses. Increased cell filamentation was observed under LSMMG upon ampicillin treatment, possibly reflecting a protective mechanism against exposure to antibiotics. These observations indicate that, in the presence of antibiotics, the survival of E. coli O157:H7 is greater under LSMMG than under NG, indicating that antibiotic therapies may need to be adjusted during space missions.